Komunikasi Dosen Dengan Mahasiswa Dalam Konteks Proses Belajar Mengajar Di Program Studi Hubungan Masyarakat Politeknik Lp3i Bandung - Farie Arief Rahman Farie (KOMVERSAL, 2022)
The outcome of education quality depends to education process. In which, all element of education process must have a solid synergy to make a quality outcomes. The communication methods that the way to give student learn can be variated, but some of that methods isn’t the right choice to be done by the lecturer in a class. This journal try to find what kind of methods that being likely by student to boost student motivation in class. This research used descriptive research methodology, to the all student in public relations major of politeknik lp3i bandung. Theres are 53 sample are choosed is the student who being wrote a questioner by simply ramdong sampling. Based on research, many lecturers have done the correct method since the beginning. Communication that produce by lecturer about education process agreement to get a good benchmark for lecturers to organize students in the classroom are fair enough.